Research progress on rheumatoid arthritis-associated depression - Liu, Nian; Yan, Weitian; Su, Rong; Zhang, Lin; Wang, Xingqiang; Li, Zhaofu; Qin, Dongdong; Peng, Jiangyun (Frontiers in Behavioral Neuroscience, 2023)
Depression is an independent mood disorder and one of the most common comorbidities of rheumatoid arthritis (RA). Growing evidence suggests that there is two-way regulation between RA and depression, resulting in a vicious cycle of RA, depression, poor outcomes, and disease burden. The rising prevalence of RA-associated depression warrants a re-examination of the relationships between them. Here we provide an overview of the etiology and pathological mechanisms of RA-associated depression, and recent advances in treatment with biologics, which will facilitate the development of new and effective prevention and treatment strategies.